2003
DOI: 10.1002/ccd.10409
|View full text |Cite
|
Sign up to set email alerts
|

Increased secretion of insulin during oral glucose tolerance test can be a predictor of stent restenosis in nondiabetic patients

Abstract: Insulin is known to stimulate proliferation and migration of vascular smooth muscle cells. As the predominant mechanism of restenosis after stent implantation is neointimal tissue proliferation, one can expect a relationship between hyperinsulinemia and restenosis in these patients. The aim of this study was to determine whether hyperinsulinemia during oral glucose tolerance test is a predictor of the development of restenosis after stent implantation in nondiabetic patients. We prospectively studied 52 nondia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…33) Takagi et al 34) have shown that the neointimal index that was measured six months after coronary stenting correlated with the fasting and post-glucose load insulin levels. Babalik et al 35) have demonstrated that hyperinsulinemia during the OGTT was a strong predictor of restenosis at the six month follow-up. Insulin resistance in diabetics aggravates coronary restenosis through a direct growth factor-like effect of insulin on the vascular smooth muscle and neointimal cells.…”
Section: Pathophysiologic Mechanisms Of Coronary Restenosismentioning
confidence: 99%
“…33) Takagi et al 34) have shown that the neointimal index that was measured six months after coronary stenting correlated with the fasting and post-glucose load insulin levels. Babalik et al 35) have demonstrated that hyperinsulinemia during the OGTT was a strong predictor of restenosis at the six month follow-up. Insulin resistance in diabetics aggravates coronary restenosis through a direct growth factor-like effect of insulin on the vascular smooth muscle and neointimal cells.…”
Section: Pathophysiologic Mechanisms Of Coronary Restenosismentioning
confidence: 99%
“…Insulin has several biological properties, which may be related to the process of restenosis. In fact, some argue that insulin resistance, rather than diabetes, is a more important predictor of restenosis [5]. In the era of the drug‐eluting stent, perhaps a more careful look at the cell cycle may provide important insight regarding the efficacy of stent‐based delivery of sirolimus and other drugs for the prevention of restenosis in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin has several biological properties, which may be related to the process of restenosis. In fact, some argue that insulin resistance, rather than diabetes, is a more important predictor of restenosis [5]. In the era of the drug-eluting stent, perhaps a more careful look at the cell cycle may provide important insight regarding the efficacy of stentbased delivery of sirolimus and other drugs for the prevention of restenosis in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%